Stoma-Related Complications: Frequency of Postoperative Morbid Events and Factors Related to Adverse Outcomes - Zubillaga-Mares, Asya; Alvarez-Bautista, Francisco Emmanuel; Cárdenas-Lailson, Eduardo; Nájera-Saldaña, Alberto; Nuñez-Venzor, Alejandra; Meza-Hernández, Javier Andrés; Serrano-Sánchez, Minnet; Trejo-Ávila, Mario (Journal of Coloproctology, 2024)
Introduction Stoma placement is a common surgical procedure that can be performed in the context of urgent and elective surgery for benign and malignant conditions, with an estimated morbidity ranging from 21% to 70%.Methods A retrospective cohort analysis to determine the incidence of stoma placement postoperative-related complications and potential associated factors. This study was conducted at a single tertiary care center in Mexico City including all patients who underwent a stoma construction between January 2016 and October 2023.Results A total of 276 patients underwent stoma construction. Eighty-one (29.3%) patients presented morbidity exclusively related to the ostomy.The multivariate analysis showed the following risk factors: advanced age for developing stoma-related complications; obesity for developing parastomal hernia; strangulated hernia and complicated diverticular disease for developing mucocutaneous dehiscence; bowel obstruction and parastomal hernia for developing stomal prolapse; anastomotic leak and preoperative corticosteroid therapy for developing parastomal abscess; and end-colostomy and advanced age for reoperation.Discussion Ostomy creation carries a high morbidity rate. Preoperative features such as advanced age, obesity, corticosteroid therapy, the indication of the surgery, as well as the type of the stoma created must be considered as they could significantly impact the development of adverse outcomes.
Keywords: stoma complications; stomas; colostomy; ileostomy